A back-to-back comparison of white light video endoscopy with autofluorescence endoscopy for adenoma detection in high-risk subjects. Issue 6 (13th May 2010) - Ramsoekh, Dewkoemar; Haringsma, Jelle; Poley, Jan Werner; van Putten, Paul; van Dekken, Herman; Steyerberg, Ewout W; van Leerdam, Monique E; Kuipers, Ernst J
Abstract : Objective: To compare the sensitivity of autofluorescence endoscopy (AFE) and white light video endoscopy (WLE) for the detection of colorectal adenomas in high-risk patients belonging to Lynch syndrome (LS) or familial colorectal cancer (CRC) families. Methods: This was a prospective single-centre study carried out in a tertiary referral centre. The subjects were 75 asymptomatic patients originating from LS or familial CRC families. Patients were examined with either WLE followed by AFE or AFE followed by WLE. Back-to-back colonoscopy was performed by two blinded endoscopists. All lesions were removed during the second endoscopic procedure. Lesions missed during the second procedure were identified and removed on third pass. The sensitivity calculations for colorectal adenomas were based on histology results. The main outcome measures were the difference in sensitivity between WLE and AFE for the detection of adenomas in patients with LS or familial CRC. Results: At least one adenoma was detected in 41 (55%) patients. WLE identified adenomas in 28/41 patients and AFE in 37/41 patients, corresponding to a 32% increase. In total 95 adenomas were detected, 65 by WLE and 87 by AFE, resulting in a significantly higher sensitivity of AFE compared with WLE (92% vs 68%; p=0.001). The additionally detected adenomas with AFE were significantly smaller than the adenomas detected by WLE (mean 3.0 mm vs 4.9 mm, p<0.01). Conclusions: AFE improves the detection of colorectal adenomas in patients with LS or familial CRC. The results of this study suggest that AFE may be preferable for surveillance of these high-risk patients.